THE EFFECT OF HALAL CERTIFICATION, PRODUCT QUALITY, SERVICE QUALITY, ON CONSUMER SATISFACTION OF MIXUE PRODUCTS - Febrianti, Dina Deltalia; Santoso, Budi; Setianingsih, Wahyu Eko (Univesitas Muhammadiyah Tangerang, 2024)
Every company will always try to make a strategy to maintain the sustainability of its company. The business that is currently competing is a business that produces food or beverages, this is because food or beverage products are always needed by everyone, so there are many companies competing to produce these products with several flavor variants and certain menus. This study aims to determine the effect of halal certification variables (X1), product quality (X2) and service quality (X3) on consumer satisfaction (Y) of the Mixue Jember ice cream outlet. This type of research is quantitative research with a sample size of 98 respondents. Sampling used probability sampling with proportionate stratified random sampling technique. The data collection techniques used are data instrument testing, classical assumption testing, multiple linear analysis, hypothesis testing and coefficient of determination (R2). The data obtained were then analyzed using multiple linear regression with the help of SPSS. The results of this study indicate that the variables of halal certification, product quality and service quality have a positive and significant effect on consumer satisfaction of the Mixue Jember ice cream outlet.